Analisis Dampak Profitabilitas Terhadap Harga Saham Pada Perusahaan Sektor Infrastruktur - Setiawan Setiawan; Dimas Sumitra Danisworo; Nur'aeni Nur'aeni; Alexander Bima Sandra (Universitas Ma'soem, 2021)
Indonesia needs a lot of infrastructures to continue to support its economic growth. This has attracted investors to invest in infrastructure companies. However, companies must show high profitability so that investors are more interested so that the company's shares can continue to rise. This study aims to reveal the effect of profitability on stock prices in infrastructure sector companies in Indonesia. The research method is associative which looks at the pattern of relationships between research variables. Based on data collection, there were 188 observations of companies engaged in the infrastructure sector for the period 2016 to 2018. The data analysis was SEM-PLS. The results reveal that only Earning per Share (EPS) has a significant effect on stock prices. The effect formed is positive with a significance level of below 5%.